An algorithm for deriving equations of motion of constrained mechanical system - Phong, Dinh Van (Vietnam Journal of Mechanics, 1999)
The article deals with the form of equations of motion of mechanical system with constraints. For holozoic systems the number of differential equation is equal to the degrees of freedom, without regard to the number of chosen coordinates. The possibilities of computer processing (symbolical and numerical) are shown. Two simple examples demonstrate the described technique.